Comparative Pharmacokinetics and Pharmacodynamics of Bococizumab Following a Single Subcutaneous Injection Using Drug Substance Manufactured at Two Sites or Administration via Two Different Devices. Issue 1 (24th April 2018) - Wang, Ellen Q.; Plotka, Anna; Salageanu, Joanne; Baltrukonis, Daniel; Mridha, Khurshid; Frederich, Robert; Sullivan, Beth E.
Abstract: The pharmacokinetics (PK) and pharmacodynamics (PD) of bococizumab, a proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor, were compared following a single 150‐mg subcutaneous dose administered to healthy subjects (n = 156–158/arm) via: (1) a prefilled syringe (PFS) using drug substance (DS) manufactured by Pfizer, (2) a PFS using DS manufactured by Boehringer Ingelheim Pharma, (3) a prefilled pen using DS manufactured by Pfizer (NCT02458209). Blood samples were collected for 12 weeks postdose. Safety was monitored throughout. Mean maximum plasma concentration (Cmax ) ranged between 11.0 and 11.3 μg/mL, and area under the plasma concentration‐time curve (AUCinf ) ranged between 177.6 and 185.0 μg·day/mL across treatments. The 90% confidence intervals for the ratios of adjusted geometric means for Cmax and AUCinf fell within the 80%–125% range for both DS and delivery device comparisons. Comparable low‐density lipoprotein cholesterol profiles were observed, with nadir values of 54.3–56.1 mg/dL across treatments. Similar PCSK9 responses were also observed. Safety profiles were similar across treatments, and the majority of adverse events (AEs) were mild. Three subjects reported serious AEs. The most frequently reported AEs were headache, injection‐site reaction, and upper respiratory tract infection, with no clear differences across treatments. Comparable PK, PD, and safety were observed following a single bococizumab 150‐mg subcutaneous injection regardless of site of DS manufacture or delivery device used.